Chill - Thompson, Carol (Surry Hills, N.S.W. : Little Hare Books, 2010)
Dolly and Jack fall out over portraits they have painted of each other. They are so offended they can hardly breathe. But as they calm down they discover it is not their collections, or their bubble baths they love the best, but one another.